2023
DOI: 10.3390/ijms24076073
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cholinesterase and Anti-α-Amylase Activities and Neuroprotective Effects of Carvacrol and p-Cymene and Their Effects on Hydrogen Peroxide Induced Stress in SH-SY5Y Cells

Abstract: Several researchers have demonstrated the health and pharmacological properties of carvacrol and p-cymene, monoterpenes of aromatic plants. This study investigated these compounds’ possible anti-cholinesterase, anti-α-amylase, and neuroprotective effects. We evaluated the anti-acetylcholinesterase and anti-α-amylase activities at different concentrations of the compounds. The maximum non-toxic dose of carvacrol and p-cymene against SH-SY5Y neuroblastoma cells was determined using an MTT assay. The neuroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…The IC 50 value for Carvacrol obtained in our experiment was similar to previously obtained values of 288.26 µM (43.29 µg/mL) [46] and 91.7 µg/mL [29]. However, a recent study reported a lower IC 50 value (3.8 µg/mL) for Carvacrol and Galantamine (0.6 µg/mL) [47].…”
Section: In Vitro Anti-acetylcholinesterase Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…The IC 50 value for Carvacrol obtained in our experiment was similar to previously obtained values of 288.26 µM (43.29 µg/mL) [46] and 91.7 µg/mL [29]. However, a recent study reported a lower IC 50 value (3.8 µg/mL) for Carvacrol and Galantamine (0.6 µg/mL) [47].…”
Section: In Vitro Anti-acetylcholinesterase Activitysupporting
confidence: 90%
“…µg/mL [29]. However, a recent study reported a lower IC50 value (3.8 µg/mL) for Carvacrol and Galantamine (0.6 µg/mL) [47]. The mode of inhibition of the Carom extracts, Carvacrol, and Thymol was analyzed using the Lineweaver-Burk plot.…”
Section: In Vitro Anti-acetylcholinesterase Activitymentioning
confidence: 99%
“…Compared with other compounds, terpinene-4-ol had a comparable (−7.2 kcal/mol) while linalool had a superior affinity (−8.1 kcal/mol) with PTGS2. A previous study explored the protective effect of p-cymene in H 2 O 2 -induced SH-SY5Y cells ( Caputo et al, 2023 ). In our study, pretreatment with this compound can enhance cell viability and LDH over-release in CORT-induced PC12 cells, confirming the neuroprotective potential of p-cymene in different in vitro models of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The AChE and BChE inhibitory assays were performed according to a described spectrophotometric method [ 23 ] with some modifications [ 24 ]. The α-amylase assay was carried out following Bernfeld’s protocol [ 25 ] with some modifications.…”
Section: Methodsmentioning
confidence: 99%